Innovation. An Instrument for Development of Companies - Ana-Maria Nica; Ion Stancu; Dumitra Stancu (Amfiteatru Economic Journal, 2017)
Innovation is seen in numerous specialized studies as an efficient method for improving the performance of a company based on the sector in which that company operates. Based on this idea, the article aims to determine the nature of inter-correlation between the innovation activity of companies and the level of performance of these, which are the main types of innovation and how they can influence companies' position and how the sector of activity can influence the dimension of the impact of innovation. For achieve these objectives have been analysed empirical studies in various sectors, studies which have highlighted a positive inter-correlation between innovation activity and the performance of companies with significant differences depending on the type of innovation and industry use. The article is completed by an empirical analysis which aims to determine the extent to which performance of companies in the construction sector is sensitive to innovation activity. For the analysis were collected data from 14 companies which developed the specific activities in the construction sector of Europe, were achieve a total of 112 observations. The results obtained by applying a multiple regression model shows a positive correlation relationship between indicators of innovation (R&D expenditures and the value of patents/patents) on the one side and performance indicators (equity, labour productivity and number of employees) on the other side. Another direction of research analysed in this paper is to determine the impact of labour indicators on the level of innovation, in this situation was achieve a positive but insignificant inter-correlation between those indicators.
Keywords: C31; D24; L25; 330; Innovation; development; construction sector; performance